The Development And Application Of The Zakat Collection Blockchain System - Khairil Faizal Khairi; Nur Hidayah Laili; Hisham Sabri; Azuan Ahmad; Van Hieu Pham; Manh Dung Tran (Virtus Interpress, 2024)
Indexed by Scopus